2021
DOI: 10.3389/fcell.2021.673291
|View full text |Cite
|
Sign up to set email alerts
|

Iron Overload-Induced Ferroptosis Impairs Porcine Oocyte Maturation and Subsequent Embryonic Developmental Competence in vitro

Abstract: Accumulating evidence indicates that ferroptosis is an iron-dependent form of regulated cell death. This type of iron-dependent programmed cell death is different from traditional forms of regulated cell death, such as apoptosis and autophagy. However, the role of ferroptosis in porcine oocyte maturation and the associated mechanism remain unclear. In the present research, we investigated the effects of ferric ammonium citrate (FAC), a specific ferroptosis inducer, on porcine oocyte meiotic maturation and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…The suppression of the proliferation of artesunate was accompanied by cell cycle blockade and modification of cell cycle molecules [ 38 ]. Hu et al found that iron overload-induced ferroptosis disrupted meiosis and lowered the quality of pig oocytes potentially owing to enhanced oxidative stress, mitochondrial malfunction, and autophagy activation [ 39 ]. The low-risk group in the predictive model had fewer KEGG enrichment values.…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of the proliferation of artesunate was accompanied by cell cycle blockade and modification of cell cycle molecules [ 38 ]. Hu et al found that iron overload-induced ferroptosis disrupted meiosis and lowered the quality of pig oocytes potentially owing to enhanced oxidative stress, mitochondrial malfunction, and autophagy activation [ 39 ]. The low-risk group in the predictive model had fewer KEGG enrichment values.…”
Section: Discussionmentioning
confidence: 99%
“…However, safety issues for infertile patients with EMs should be further considered. Our study demonstrates the harm of an iron overload environment to the oocyte, and relevant studies have proposed that iron overload-induced ferroptosis impairs oocyte maturation and development [ 49 ]. Iron overload was thought to play an important contributory role in shaping the EMs inflammatory microenvironment and cell adhesion [ 6 , 15 , 27 ].…”
Section: Discussionmentioning
confidence: 62%
“…Dysregulation of follicle fatty acids is a potential driver of human POI, as free fatty acid treatment reduces the proliferation rate and induces obvious apoptosis signals in granulosa cells isolated from the ovaries 56 . Iron overload-induced ferroptosis may suppress the meiotic process during porcine oocyte maturation and lead to oxidative stress in each stage of the follicles, thus disturbing follicle development [57][58][59] . Here, we found that BNC1 is required for maintaining mitochondrial function and lipid metabolism in oocytes and deficiency of BNC1 triggers ferroptosis-dependent POI.…”
Section: Discussionmentioning
confidence: 99%